Women’s Consciousness in the Story ‘Apurnata’ - Gyawali, Pradeep Prasad (Academia Research Journal, 2023)
‘Apurnata’ is a story written by Jaleshwari Shrestha. In the presented research article, taking this story as a lesson, the meaning of the story has been analyzed and evaluated based on liberal feminism among the various branches of feminism. The main objective of this study is to find out the various aspects related to women's consciousness in this story. In this, awareness of gender discrimination related to feminism, awareness of exploitation and oppression, awareness of sexual exploitation and violence against women, awareness of women's existence and identity and awareness of class discrimination have been analyzed as a theoretical framework. In this story, due to patriarchy, men are allowed to move freely, eat, drink and have fun, but women have to be aware step by step, they have to stay locked up at home, and under the guise of religious beliefs, patriarchy discriminates against women by inciting men to polygamy, and if they want to have a son, they are threatened. It has been expressed that men who have created a feeling of discrimination towards sons and daughters should not pay attention to domestic work, but women have to do domestic work and bear children and take care of them. This story has awakened awareness that we should fight against oppression based on gender. In this story, the struggle of a man trying to end the existence and identity of a woman and a woman trying to protect it is presented. It also expresses the idea that women should not be kept as a means of enjoyment and a factory for giving birth to children. Here, because the poor women are poor, the reality of double oppression has been presented and the consciousness has been awakened that they should not tolerate such discrimination and humiliation and should be punished through legal remedies.